The mammalian Ire1 inhibitor, 4µ8C, exhibits broad anti-Aspergillus activity in vitro and in a treatment model of fungal keratitis - Kamath, Manali M.; Adams, Emily M.; Lightfoot, Jorge D.; Wells, Becca L.; Fuller, Kevin K. (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveThe fungal unfolded protein response consists of a two-component relay in which the ER-bound sensor, IreA, splices and activates the mRNA of the transcription factor, HacA. Previously, we demonstrated that hacA is essential for Aspergillus fumigatus virulence in a murine model of fungal keratitis (FK), suggesting the pathway could serve as a therapeutic target. Here we investigate the antifungal properties of known inhibitors of the mammalian Ire1 protein both in vitro and in a treatment model of FK.MethodsThe antifungal activity of Ire1 inhibitors was tested against conidia of several A. fumigatus isolates by a broth microdilution assay and against fungal biofilm by XTT reduction. The influence of 4μ8C on hacA mRNA splicing in A. fumigatus was assessed through gel electrophoresis and qRT-PCR of UPR regulatory genes. The toxicity and antifungal profile of 4μ8C in the cornea was assessed by applying drops to uninfected or A. fumigatus-infected corneas 3 times daily starting 4 hours post-inoculation. Corneas were evaluated daily through slit-lamp imaging and optical coherence tomography, or at endpoint through histology or fungal burden quantification via colony forming units.ResultsAmong six Ire1 inhibitors screened, the endonuclease inhibitor 4μ8C displayed the strongest antifungal profile with an apparent fungicidal action. The compound both blocked conidial germination and hyphal metabolism of A. fumigatus Af293 in the same concentration range that blocked hacA splicing and UPR gene induction (60-120 µM). Topical treatment of sham-inoculated corneas with 0.5 and 2.5 mM 4μ8C did not impact corneal clarity, but did transiently inhibit epithelialization of corneal ulcers. Relative to vehicle-treated Af293-infected corneas, treatment with 0.5 and 2.5 mM drug resulted in a 50% and >90% reduction in fungal load, respectively, the latter of which corresponded to an absence of clinical signs of infection or corneal pathology.ConclusionThe in vitro data suggest that 4μ8C displays antifungal activity against A. fumigatus through the specific inhibition of IreA. Topical application of the compound to the murine cornea can furthermore block the establishment of infection, suggesting this class of drugs can be developed as novel antifungals that improve visual outcomes in FK patients.